FINANCIAL IMPLICATIONS OF INTEREST BY UPDATING LATE PAYMENT OF TAX DEBT - Valencia Gutiérrez, Adolfo (2012)
The birth of a tax that is set by the enactment of a law or a legislative decree in case of delegation considered exhaustively in Article 74 of the Political Constitution of Peru, within the technical tax which also clearly typifies the birth of the obligation tax set out in Article 2 of the Tax Code states: the tax liability arises when performing the action described in the law, as a generator of the this obligation, which is public law and is the link between the creditor and the debtor, established by law, which aims at providing tax compliance, being coercively enforceable under Article 1 of the Tax Code. That is why once the tax liability arise these is only the fact of being satisfied with the compliance tax provision, whether substantive or formal, and failure of timely payment of money can generate interest referred to in tax regulations which have financial implications for the taxpayer, it is clear that by the late payment of the same, the state is obliged to demand interest payments as a form of compensation for the good provided.